The Future of Institutional Repositories - Francisco José GARCÍA PEÑALVO (Ediciones Universidad de Salamanca, 2017)
The institutional repositories are a fundamental component in the Open Science technological ecosystem. The green route for Open Access falls on them and, therefore, they are key in the new research policies that are described in the laws of science of many countries. They also play a highly relevant role in the value chain of the visibility and scientific reputation of a researcher. However, repositories are a distant tool for most researchers, which translates into loss of opportunity for them, loss of competitiveness for the institutions that support the repositories and, ultimately, a loss for society in general. That is why this paper reflects on how these institutional repositories should evolve in order to attract and retain the attention of researchers in order to achieve they can introduce them into their workflows within the cycle of their research.